Use of nanofiltration concentrates of buttermilk and whey for fermented dairy products with increased mass content of protein - N. G. Ostreczova; A. V. Bobrova (Пищевые системы, 2021)
Baromembrane methods, in particular, nanofiltration, open up broad opportunities in the field of obtaining dairy products with a high protein content in terms of quality and energy saving. This paper describes the feasibility of using buttermilk and cheese whey concentrates obtained by nanofiltration in the production of fermented milk products. The physicochemical, rheological and organoleptic studies of nanofiltration concentrates of buttermilk and cheese whey made it possible to select concentrates with a mass fraction of dry substances of 20% for further research. Electron microscopic studies of the microstructure of buttermilk, whey and their concentrates with a mass fraction of dry substances of 20% showed that when buttermilk was concentrated by nanofiltration, the average diameter of dispersed particles did not increase and amounted to (130 ± 30) nm. The grid cells size decreased by 3.2 times; in serum concentration, the particle size increased by 1.7 times with a decrease in the grid cells size by 1.3 times. The obtained data make it possible to predict the positive effect of this concentration method on the consistency of fermented milk products. The use of the combined milk base with a ratio of buttermilk concentrate (20% dry matter) to whey concentrate (20% dry matter) of 50:50 and 75:25 is substantiated, providing a complete protein content of 4.4–5.6% in fermented milk products. A high rate of acid formation and a good water-holding capacity of acid clots were established when fermenting with a starter culture containing thermophilic streptococcus and acidophilic bacillus in a ratio of 4:1. The obtained results make it possible to expand the range of fermented milk products with an increased mass fraction of protein for good nutrition of the population.